High-depth fluorescence imaging using a two-photon FRET system for mitochondrial pH in live cells and tissues - Chang, Min Jung; Kim, Kyutae; Park, Kyun Seob; Kang, Ji Su; Lim, Chang Su; Kim, Hwan Myung; Kang, Chulhun; Lee, Min Hee (Chemical Communications, 2018)
We developed a fluorescent pH probe (1) capable of two-photon excitation and far-visible-emission based on FRET, composed of naphthalimide-piperazine-rhodamine. It exhibited a pH-dependent reversible and fast ratiometric fluorescence change in the rhodamine emission. Probe 1 was applied to image the pH perturbations of mitochondria in living cells and tissues.
Keywords: Fluorescence; Fluorescence Resonance Energy Transfer; Fluorescent Dyes; HeLa Cells; Humans; Hydrogen-Ion Concentration; Microscopy, Confocal; Mitochondria; Naphthalimides; Photons; Piperazines; Rhodamines